2015
DOI: 10.1021/acschembio.5b00648
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Dystrophy Mutations Impair the Nuclear Envelope Emerin Self-assembly Properties

Abstract: More than 100 genetic mutations causing X-linked Emery–Dreifuss muscular dystrophy have been identified in the gene encoding the integral inner nuclear membrane protein emerin. Most mutations are nonsense or frameshift mutations that lead to the absence of emerin in cells. Only very few cases are due to missense or short in-frame deletions. Molecular mechanisms explaining the corresponding emerin variants’ loss of function are particularly difficult to identify because of the mostly intrinsically disordered st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(64 citation statements)
references
References 41 publications
16
48
0
Order By: Relevance
“…Figure 2A shows that long curvilinear filaments were detected for EmN, as reported earlier [25], and also for EmN132. Therefore, we incubated the different fragments at a fixed concentration of 600 lM during 1 week at 293 K. We then observed the samples using negative staining electron microscopy.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Figure 2A shows that long curvilinear filaments were detected for EmN, as reported earlier [25], and also for EmN132. Therefore, we incubated the different fragments at a fixed concentration of 600 lM during 1 week at 293 K. We then observed the samples using negative staining electron microscopy.…”
Section: Resultssupporting
confidence: 85%
“…1A) is composed of a globular LEM domain, from residue 1 to residue 45 [28], and a large intrinsically disordered region, from residue 46 to residue 187 [25,29]. 1A) is composed of a globular LEM domain, from residue 1 to residue 45 [28], and a large intrinsically disordered region, from residue 46 to residue 187 [25,29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the relevance of this redistribution to EDMD pathology is unclear even in the patients where it was observed. One recent study suggested a link between emerin cytoplasmic accumulation and pathology in that emerin-p.P183T assembles into oligomers that perhaps cannot pass through the peripheral channels of the nuclear pore complexes [38]. Nonetheless, unlike this particular case, most reported emerin mutations result in a loss of protein.…”
Section: Discussionmentioning
confidence: 77%